Buddhist concept of assimilation - Gnanaseeha, Rambukewela (Singapore Samadhi Buddhist Society, 2006)
chapter I. Development of the concepts of Buddha and Bodhisattva -- the early background -- chapter II. Development of the concepts of Buddha and Bodhisattva in the schools of Buddhism -- chapter III. Development of the concepts of Buddha and Bodhisattva in Mahāyāna Buddhism -- chapter IV. Religious syncretism of the concepts of Buddha and Bodhisattva in Mahāyāna Buddhism -- chapter V. Religious syncretism and the Buddhist of art -- chapter VI. Religious syncretism as depicted in the Buddhist art -- chapter VII. Ethical and social importance of religious syncretism
Includes bibliographical references (pages 170-173) and index
Archivierung prüfen
Archivierung/Langzeitarchivierung gewährleistet
Keywords: Buddhism -- Doctrines; Buddhism -- Relations